Her last breath - Castillo, Linda (Castillo, Linda. Kate Burkholder novel., 2013)
When her best friend's husband and two children are killed in a suspicious car accident, Amish community member Kate Burkholder maintains a vigil by a grievously injured survivor who may hold answers before investigating a brutal killer who makes her question everything about her Amish culture.